Passive Control of the Flow Around a Rectangular Cylinder with a Custom Rough Surface - Mario A. Aguirre-López; Filiberto Hueyotl-Zahuantitla; Pedro Martínez-Vázquez; José Ulises Márquez-Urbina (Fluids)
Motivated by existing techniques for implementing roughness on cylinders to control flow disturbances, we performed delayed detached eddy simulations (DDES) at Re = <semantics>6×106</semantics> that generated unsteady turbulent flow around a rectangular cylinder with a controlled wrinkled surface and a 1:4 aspect ratio. A systematic study of the roughness effect was carried out by implementing different configurations of equally spaced grooves and bumps on the top-surface of the cylinder. Our results suggest that groove geometries reduce energy dissipation at higher rates than the smooth reference case, whereas bumped cylinders produce relative pressures characterized by a sawtooth pattern along the middle-upper part of the cylinder. Moreover, cylinders with triangular bumps increase mean drag and lift forces by up to 8% and 0.08 units, respectively, while circular bumps increase vorticity and pressure disturbances on the wrinkled surface. All of these effects impact energy dissipation, vorticity, pressure coefficients, and flow velocity along the wrinkled surface. Both the surface-manufactured cylinders and the proposed visualization techniques could be replicated in a variety of engineering developments involving flow characterization in the presence of roughness.